Efficacy and safety of totally laparoscopic gastrectomy with uncut Roux-en-Y for gastric cancer: a dual-center retrospective study - Yizhen Chen; Yuanyuan Zheng; Song Tan; Yifan Chen; Tao Zheng; Shaolin Liu; Yulong Mi; Shentao Lin; Changshun Yang; Jian Jiang; Weihua Li (World Journal of Surgical Oncology)
Abstract Background Uncut Roux-en-Y (URY) effectively alleviates the prevalent complexities connected with RY, such as Roux-en-Y stasis syndrome (RSS). Nevertheless, for gastric cancer (GC) patients, it is still controversial whether URY has an impact on long-term prognosis and whether it has fewer afferent loop recanalization. Therefore, compare whether URY and RY have differences in prognosis and long-term complications of GC patients undergoing totally laparoscopic gastrectomy (TLG). Methods We analyzed the data of patients who underwent TLG combined with digestive tract reconstruction from dual-center between 2016 and 2022. Only patients undergoing URY and RY were selected for analysis. Relapse-free survival (RFS) and overall survival (OS) were estimated. Bias between the groups was reduced by propensity score matching (PSM). The Cox proportional hazard regression model was used to further analyze the influence of URY on prognosis. Results Two hundred forty two GC patients were enrolled. The URY had significantly shorter operation time, liquid food intake time, and in-hospital stays than the RY (P < 0.001). The URY had fewer long-term and short-term postoperative complications than the RY, especially with regard to RSS, reflux esophagitis, and reflux gastritis. The 3-year and 5-year OS of the URY group and the RY group before PSM: 87.5% vs. 65.6% (P < 0.001) and 81.4% vs. 61.7% (P = 0.001). PSM and Cox multivariate analysis confirmed that compared to RY, URY can improve the short-term and long-term prognosis of GC patients. Conclusion TLG combined with URY for GC, especially for advanced, older, and poorly differentiated patients, may promote postoperative recovery and improve long-term prognosis.